2015
DOI: 10.1111/jiec.12277
|View full text |Cite
|
Sign up to set email alerts
|

Goods Movement Life Cycle Assessment for Greenhouse Gas Reduction Goals

Abstract: SummaryThe formation of effective policies to reduce emissions from goods movement should consider local and remote life cycle effects as well as barriers for mode shifting. Using uniand multimodal freight movements by truck, rail, and ocean-going vessel (OGV) associated with California, a life cycle assessment (LCA) is developed to estimate the local and remote emissions that occur from freight activity inside and associated with the state. Long-run average per tonne-kilometer results show that OGVs emit the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 12 publications
0
33
0
Order By: Relevance
“…Thus, the model captures important improvements both in material production and in the electricity used in manufacturing. The THEMIS model is documented in a separate method paper [16] and has been applied in a number of assessments [19][20][21][22][23][24][25][26].…”
Section: Lca Modelmentioning
confidence: 99%
“…Thus, the model captures important improvements both in material production and in the electricity used in manufacturing. The THEMIS model is documented in a separate method paper [16] and has been applied in a number of assessments [19][20][21][22][23][24][25][26].…”
Section: Lca Modelmentioning
confidence: 99%
“…Technology projection and life cycle impact profiles of average 60 W-equivalent 900 lm A19 lamps. (Sources: Bergesen et al [29], Nahlik et al [37], DOE [3,13,14,35,36], DOL [39], EIA [47], EPA [44,45] [35]. It is expected that both IL and HL are being phased out of operation by EISA [6].…”
Section: Technology Projection and Life Cycle Impact Profilesmentioning
confidence: 99%
“…The transportation stage represents only the transportation between the original equipment manufacturer suppliers (defined per DOE's study) and the retailer (assumed at the geographical center of the continental US (Kansas). It accounts for LED weight reduction, [3] improved vehicle technology, and lowercarbon fuels, the latter two of which would decrease the life cycle energy factor and GHG emission factor by 57% and 91% respectively for bunker fuel container ships, and 58% and 56% respectively for diesel trucks by 2050 [37].…”
Section: Technology Projection and Life Cycle Impact Profilesmentioning
confidence: 99%
“…To estimate these savings, we utilized existing lifecycle assessment analyses by Nahlik et al (2015) and Facanha and Horvath (2007). These authors found that, due to the fuel efficiencies of rail as compared to trucks, greenhouse-gas emissions associated with freight trains were 0.44 pound lower per ton-mile than emissions associated with trucks (0.11 pound compared to 0.55 pound per ton-mile).…”
Section: Potential Benefitsmentioning
confidence: 99%